Impaired Cerebral Autoregulation After Subarachnoid Hemorrhage: A Quantitative Assessment Using a Mouse Model - Koide, Masayo; Ferris, Hannah R.; Nelson, Mark T.; Wellman, George C. (Frontiers in Physiology, 2021)
Subarachnoid hemorrhage (SAH) is a common form of hemorrhagic stroke associated with high rates of mortality and severe disability. SAH patients often develop severe neurological deficits days after ictus, events attributed to a phenomenon referred to delayed cerebral ischemia (DCI). Recent studies indicate that SAH-induced DCI results from a multitude of cerebral circulatory disturbances including cerebral autoregulation malfunction. Cerebral autoregulation incorporates the influence of blood pressure (BP) on arterial diameter in the homeostatic regulation of cerebral blood flow (CBF), necessary for maintaining constant brain perfusion during physiological swings in systemic BP. In this study, we quantitatively examined the impact of SAH on cerebral autoregulation using a mouse endovascular perforation model and a newly developed approach combining absolute and relative CBF measurements. This method enables a direct quantitative comparison of cerebral autoregulation between individual animals (e.g., SAH vs control or sham-operated mice), which cannot be done solely using relative CBF changes by laser Doppler flowmetry. Here, absolute CBF was measured via injection of fluorescent microspheres at a baseline BP. In separate groups of animals, in vivo laser Doppler flowmetry was used to measure relative CBF changes over a range of BP using phlebotomy and the pressor phenylephrine to lower and raise BP, respectively. Absolute CBF measurements from microspheres were then used to calibrate laser Doppler measurements to calculate the relationship between CBF and BP, i.e., “cerebral autoregulation curves”. Un-operated and sham-operated groups exhibited similar cerebral autoregulatory curves, showing comparable levels of relatively constant CBF over a range of BP from ~80 mmHg to ~130 mmHg. In contrast, SAH animals exhibited a narrower autoregulatory range of BP, which was primarily due to a decrease in the upper limit of BP whereby cerebral autoregulation was maintained. Importantly, SAH animals also exhibited a marked decrease in CBF throughout the entire range of BP. In sum, this study provides evidence of the dramatic reduction in cortical CBF and the diminished range of autoregulation after SAH. Furthermore, this novel methodology should pave the way for future studies examining pathological mechanisms and/or therapeutic strategies targeting impaired cerebral autoregulation, a pathology common to many cardiovascular and cerebrovascular disorders.